Pengaruh Qulityof Work Life dan Beban Kerja Terhadap Kinerja Karyawan KSP Kopdit Pintu Air Cabang Maumere - Amanda Yecci Noeng; Cicilia Ayu Wulandari Nuwa (Jurnal Akuntansi dan Pajak, 2024)
The research background was the pre-survey results which showed that the employees performance at Pintu Air Credit Union of Maumere Branch had not been optimal. This study aimed to (1) determine the description of employee performance, quality work of life, and workload, and (2) to determine the influence of quality work of life and workload on employee performance both partially and simultaneously. The population in this study was employees Pintu Air Credit Union of Maumere Branch, totaling 30 people. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics i.e. multiple linear regression. Hypothesis testing was done through F test and t-test. The descriptive analysis revealed the variables of employee performance, quality of work life, and workload, and were in the good category. The statistical results of the t-test showed that partially, the Workload variable had a significant negative influence on employee performance while the Quality of Work Life had a significant positive infuence on employee performance. The statistical results of the F test showed that simultaneously, the variables of Workload and Quality of Work Life had a significant influence on employee perfomance. The results of the determination analysis showed that the two independent variables in this study were able to explain the fluctuation of employee performance at the Pintu Air Credit Union of Maumere Branch by 17.567%. Keywords : Quality of Work Life, Workload, Employee Performance